THE EFFORT TO IMPROVE MATHEMATICS LEARNING ACTIVITIES BY APPLYING THE STUDENT TEAMS ACHIEVEMENT DIVISION TYPE COOPERATIVE LEARNING MODEL AT CLASS VII - Siti Nurrohmah; Romelan Hamzah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
Learning that uses expository models is teacher-centered learning, make students less actively involved in following the process of learning mathematics. Therefore, there is an effort to do to increase student learning activities. This research aims to improve mathematics learning activities by applying the Student Teams Achievement Division (STAD) in grade VII G in even Semester of State Junior High School (SMP Negeri) 3 Banguntapan Bantul Regency year academy 2019/2020. This research is a class action study consisting of two cycles. This research consists of 32 students of class VII G of SMP Negeri 3 Banguntapan Bantul Regency. The data collection technique used are observations, interviews, and field records. The instruments used are observation sheets, interview guidelines, and Field records. The test instrument used is the content validity test. The analysis of the data used is qualitative descriptive. The results showed that implementing a cooperative learning model of the STAD could increase the learning activity of mathematics in students of class VII G in grade VII G in even Semester of SMP Negeri 3 Banguntapan Bantul Regency 2019/2020. The observation results of students ' mathematical learning activities have improved from cycle I to cycle II. In the cycle I, the percentage of students ' mathematics learning activity averages 54.58% with moderate criteria. In cycle II the percentage of students ' math learning activity averages 72.04% with high criteria. The students' interviews showed that students are interested in learning mathematics using a STAD cooperative learning model.